Concerning the origin of the Codex Angus - Olivier, Jean-Marie (Buried History: The Journal of the Australian Institute of Archaeology, 2020)
The paper about Codex Angus by Gerber (2017) traced its history from 1929 when it came into the possession of Adolf Deissmann. This paper explores its history prior to that, and proposes a later date for it.